The results of amniotic membrane transplantation for primary pterygium compared with conjunctival autograft - Tananuvat N. (2014)
Purpose: To study the efficacy and safety of amniotic membrane transplantation as an adjunctive therapy after surgical excision of primary pterygium and to compare the clinical outcome with that of conjunctival autograft. Methods: Eighty-six eyes of 78 patients with primary pterygium were operated on by a single surgeon (N.T.). All patients were randomized to undergo amniotic membrane or conjunctival autograft transplantation as an adjuvant therapy after pterygium excision. Forty-four eyes in 39 patients were treated with amniotic membrane transplantation (AM group), and 42 eyes of 41 patients were treated with conjunctival autograft (CG group). Patients were followed up at 1 week, 1,3,6, and 12 months postoperation. The main outcome measurement was a recurrence rate after surgery. Results: The mean follow-up was 14.40 ± 5.4 months in the AM group and 12.35 ± 3.13 months in the CG group. There were 18 recurrences (40.9%) in the AM group and two (4.76%) in the CG group, which was significantly different among both groups (P < 0.007). The cumulative proportion that were recurrence-free at 12 months was 0.6 ± 0.15 for the AM group and 0.95 ± 0.07 for the CG group (P = 0.0003, Log-rank test). The cumulative nonrecurrence rate at 6 and 12 months in all patients stratified by age and sex was not significantly different (P = 0.28 and P = 0.9, Log-rank test). No major complications were observed in either group. Conclusion: The surgical results of primary pterygium excision followed by amniotic membrane and conjunctival autograft transplantation were compared. It was found that amniotic membrane transplantation for pterygium surgery has an unacceptably high recurrence rate.